Penegakan Hukum Terhadap Pelaku Penyimpanan dan Pengumpulan Limbah B3 Tanpa Izin (Studi Kasus Putusan Nomor: 604 K/Pid.Sus Lh/2017) - Di Vaio, Selvando; Rochmani, Rochmani (LPPM Universitas Ekasakti Padang, 2024)
The case study presented in this research is Decision Number 604 K/Pid.Sus LH/2017, the defendant named Hartono committed the crime of storing and collecting B3 waste without permission. The aim to be achieved in this research is to examine the enforcement of criminal law and the judge's considerations in handing down decisions in criminal cases regarding the storage and collection of hazardous waste in Decision Number 604 K/Pid.Sus LH/2017. The research method used in this research is doctrinal/normative legal research. Where this research is focused on examining the application of rules or norms in positive law. The results of this research show that law enforcement in Decision Number: 604 K/Pid.Sus LH/2017 has paid attention to Article 102 in conjunction with Article 59 Paragraph (4) of the Law. RI Law Number 32 of 2009 concerning Environmental Protection and Management in conjunction with Government Regulation Number 101 of 2014 concerning Management of Hazardous and Toxic Waste, Law Number 48 of 2009, Law Number 8 of 1981, and Law Number 14 of 2009 1985 as amended and supplemented by Law Number 5 of 2004 and the Second Amendment to Law Number 3 of 2009 as well as other relevant laws and regulations. The judge's considerations in this case also met the elements of justice and did not take sides towards the defendant or other parties. As well as considering the element of benefit, namely not causing unrest in social life because the Defendant has been given sanctions because of his actions which could endanger the environment and the surrounding community.